184k views
3 votes
Please answer fast! teehee

Please answer fast! teehee-example-1
User ThePengwin
by
4.8k points

2 Answers

4 votes

Answer: teeheeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeee

Explanation:

Yo u soooo cool wannaaaaaa be be friends itsa song LOL..........

User Richard Fung
by
4.6k points
4 votes

Answer:

y = 9

Explanation:

∆KLH is congruent to ∆FLH by the Hypotenuse-Leg Congruence Theorem.

Therefore,

m<KHL = m<FHL

Thus:

6y = 4y + 18

6y - 4y = 18 (subtraction property of equality)

2y = 18

y = 18/2 (division property of equality)

y = 9

User JimG
by
4.9k points